Trends of board diversity: who sits in a boardroom? / Syaiful Baharee Jaafar and Mohd Mohid Rahmat - Jaafar, Syaiful Baharee; Rahmat, Mohd Mohid (Universiti Teknologi MARA, 2021)
The diversity of a board provides good information for decision-making. In addition, having individuals from different backgrounds and having unique knowledge sets, experiences and skills lead to better governance. The objective of this study was to investigate trends of diversity in the boardroom in publicly listed Malaysian companies. The study was conducted on a sample of 337 companies listed on Bursa Malaysia with 674 observations from 2015 & 2016. The findings show that the diversity of boards with respect to gender, age, education, and ethnicity is beneficial. Most corporations prefer to appoint men to the board of directors. The results of the study show that when it comes to age and ethnicity, diversity becomes a priority for companies to compete in the open market. In addition, the findings indicate that knowledge, which is related to education and qualifications, is a very important element for sitting in the boardroom. In addition, education, diversity has a positive significance in a family firm. Family members need to be better qualified to ensure that the company is able to survive in the market for longer periods.